Testing the Effectiveness of Drip Irrigation Technique Design in Chili Cultivation on Dry Land - Suwati Suwati; Muanah Muanah; Basirun Basirun (Protech Biosystems Journal, 2023)
Dry land is productive land that can operate all year round, but with minimal water availability it is one of the obstacles for chili farmers. Therefore, the right solution for this problem is by applying drip irrigation techniques. The purpose of this research was to design and test the performance of the design on chili cultivation in dry land. This study used an experimental method with a direct experimental design on community agricultural land, by making 3 treatment groups, namely P1: surface drip irrigation, P2: subsurface drip irrigation, and P3: open channel irrigation. In this study, the parameters to be studied were designing and conducting performance tests on emitter discharge, water drop uniformity, and wetted areas. The results showed that the drip irrigation design consisted of several components, including primary reservoirs, secondary reservoirs, emitters and pressure regulators. The results of the performance test of the drip irrigation technique design can be said to be feasible to apply based on the discharge value and the drop uniformity coefficient, and the growth of chili plants, both with subsurface and above-surface drip irrigation techniques, does not have a significant effect. So it can be concluded that the method of providing water with subsurface and above-surface irrigation is both said to be effective and efficient